PEDAGOGICAL TECHNOLOGIES IN CONTEXT PROFESSIONAL TRAINING OF A MUSIC TEACHER (Pedagogy of Higher and Secondary Education, 2022)
In article the questions o f substantiation contents of pedagogical technologies in context of organization music and polyart activities are considered. Opportunities of influence art culture on musical development of pupils take into account. The choice of methods, receptions, principles of teaching as a part of pedagogical technologies in conformity with laws of arts is provided.
Keywords: 1